Association between genetically proxied PPARG activation and psoriasis vulgaris: a Mendelian randomization study - Yan Xue; Yuning Xia; Donghao Cheng; Taiyu Shi; Ping Mei; Sheng Hong (Journal of Dermatological Treatment)
Background Psoriasis is a common autoimmune disease in clinical practice, and previous observational studies have suggested that PPARG agonists such as Pioglitazone may be potential therapeutic agents. However, due to interference from various confounding factors, different observational studies have not reached a unified conclusion. We aim to evaluate the potential use of PPARG agonists for treating psoriasis from a new perspective through drug-targeted Mendelian randomization (MR) analysis.Materials and methods This study includes data on 8,876 individuals for acute myocardial infarction from GWAS, and LDL cholesterol data from 343,621 Europeans. FinnGen contributed psoriasis vulgaris data for 403,972 individuals. The DrugBank10 databases function to identify genes encoding protein products targeted by active constituents of lipid-modifying targets. A two-sample MR analysis and summary-data-based MR (SMR) analysis estimated the associations between expressions of drug target genes and symptoms of psoriasis vulgaris. A multivariable MR study was further conducted to examine if the observed association was direct association.Results SMR analysis revealed that enhanced PPARG gene expression in the blood (equivalent to a one standard deviation increase) was a protective factor for psoriasis vulgaris (beta = −0.2017, se = 0.0723, p = 0.0053). Besides, there exists an MR association between LDL mediated by PPARG and psoriasis vulgaris outcomes (beta = −3.9169, se = 0.5676, p = 5.17E-12). These results indicate that PPARG is a therapeutic target for psoriasis, suggesting that psoriasis may be a potential indication for PPARG agonists.Conclusion This study confirms that therapeutic activation of PPARG helps suppress the development of psoriasis. Psoriasis may be a new indication for PPARG agonists, such as Pioglitazone. In the future, new anti-psoriatic drugs could be developed targeting PPARG.